2021
DOI: 10.1101/2021.03.09.434371
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Quantitative proteomics of hamster lung tissues infected with SARS-CoV-2 reveal host-factors having implication in the disease pathogenesis and severity

Abstract: Syrian golden hamsters (Mesocricetus auratus) infected by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) manifests lung pathology that resembles human COVID-19 patients. In this study, efforts were made to check the infectivity of a local SARS-CoV-2 isolate in hamster model and evaluate the differential expression of lung proteins during acute infection and convalescence. The findings of this study confirm the infectivity of this isolate in vivo. Analysis of clinical parameters and tissue samples… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…In any case, much can be learned in retrospect from the early and rapid, almost global establishments of hamster models in the SARS-CoV-2 pandemic, including the indispensability of proper and complete reporting of relevant experimental procedures and standardized readout parameters, among other research quality measures. Just as essential will be the integration of single cell type and time-resolved transcriptome and proteome data, 59,82 along with established classical histopathology, IHC, and ISH methodologies. 39,61,70 Regardless of the next model species of choice, comparative veterinary pathology will be prepared and indispensable for the characterization of appropriate models, their similarities and differences to what will be known from the human condition, and for the careful development and testing of effective and safe therapies and vaccine candidates for humans.…”
Section: Lessons Learned From Hamster Models Of Covid-19mentioning
confidence: 99%
See 1 more Smart Citation
“…In any case, much can be learned in retrospect from the early and rapid, almost global establishments of hamster models in the SARS-CoV-2 pandemic, including the indispensability of proper and complete reporting of relevant experimental procedures and standardized readout parameters, among other research quality measures. Just as essential will be the integration of single cell type and time-resolved transcriptome and proteome data, 59,82 along with established classical histopathology, IHC, and ISH methodologies. 39,61,70 Regardless of the next model species of choice, comparative veterinary pathology will be prepared and indispensable for the characterization of appropriate models, their similarities and differences to what will be known from the human condition, and for the careful development and testing of effective and safe therapies and vaccine candidates for humans.…”
Section: Lessons Learned From Hamster Models Of Covid-19mentioning
confidence: 99%
“…As an interesting alternative, much progress has been made in recent years in the fields of spatial proteomics and transcriptomics, which allows the quantification of the individual expression levels of virtually all proteins and mRNA molecules with single cell–type resolution. Fortunately, these have already been applied to characterize the pathology and immune responses in SARS-CoV-2-infected Syrian hamsters, 59,82 allowing for direct comparisons with similar data derived from human patients. 59 Clearly, this methodological progress inaugurates a new era in the understanding of infection pathology and immune responses on the molecular level in a cell type– and time-dependent resolution.…”
Section: Technical Limitations Of Hamster Modelsmentioning
confidence: 99%
“…Throughout this study, hemizygous hACE2 mice were used for the SARS-CoV-2 infection. The hACE2 and hACE2 ; Irgm1 −/− were inoculated with 5X10 4 (low-dose) or 5X10 5 (high-dose) plaque-forming units (PFU) via the intranasal route with highly infectious early SARS-CoV-2 strain of clade 19A (Kumar et al, 2021; Singh et al, 2022; Suresh et al, 2021) (Genbank Accession MW559533). For the low-dose experiment, the mice were sacrificed on the 6 and 15 days post-infection (DPI), whereas for the high-dose experiment, mice were sacrificed on the 7 DPI ( Figure 1A ).…”
Section: Resultsmentioning
confidence: 99%
“…Suresh et al [ 97 ] evaluated the proteomic alteration in SARS-CoV-2 infection using this animal model. Although the study had some limitations, such as sample size and experimental conditions, they found alterations in the complement system pathway, coagulation dysregulation and programmed cell death.…”
Section: Animal Modelsmentioning
confidence: 99%